Cutis marmorata telangiectatica congenita - Vinoth N Ponnurangam; Venkataraman Paramasivam (Wolters Kluwer Medknow Publications, 2014)
Cutis marmorata telangiectatica congenita (CMTC) is an uncommon, congenital, vascular malformation, characterised by a fixed, generalised or localised, reticulate erythematous rash. We report an eighty day old male child who presented with the above lesion involving the left upper and lower limbs with underlying atrophic changes.